Factors Relating to Incident Level of Stunting In Toddler (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2024)
Backgrounds: Stunting is a condition of failure to thrive in infants and toddlers resulting from chronic malnutrition, especially in the first 1,000 days of life so children are too short for their age. Stunting is caused by various factors. Stunting District. Kep. Selayar is still quite high, especially at the Barugaia District Health Center. Bontomanai with a total of 92 stunted toddlers. This study aims to determine the relationship between the history of exclusive breastfeeding, the nutritional status of toddlers, parental knowledge, and family income with the incidence of stunting in the Barugaia Community Health Center working area.Method: This type of research is quantitative with a case-control research design. This research consisted of 80 samples using cluster random sampling techniques. Data analysis was carried out using the chi-square test.Results: The results showed that 90.2% of respondents who were not exclusively breastfed experienced stunting (p: 0.000), 100% of respondents with poor nutritional status experienced stunting (p: 0.000), 96.4% of respondents with less parental knowledge experienced stunting (p: 0.000) 80.9% of respondents with family income < MSEs experienced stunting (p: 0.000).Conclusion: From this study, it can be concluded that a history of exclusive breastfeeding, nutritional status of toddlers, parental knowledge, and family income are related to the incidence of stunting. Therefore, there is a need to provide information regarding the prevention and management of stunting to the community